MANAJEMEN KEARSIPAN DALAM PENINGKATAN MUTU PELAYANAN DI DINAS PENDIDIKAN KOTA BATU - Aini, Nur (Ulul Amri: Jurnal Manajemen Pendidikan Islam, 2024)
Management plays an important role for an organization in providing order in carrying out all its work. One of the jobs that requires management is archives. Good and effective archive management can make it easier for an institution to provide the services and information its customers need. So, with this archive management it can improve the quality of services provided. The purpose of this research is to describe archival planning in improving the quality of services at the Batu City Education Service, describe the implementation of archives in improving the quality of services at the Batu City Education Office, and to describe the evaluation of the implementation of archives in improving service quality at the Batu City Education Office. This research uses qualitative research with a descriptive approach. The data collection techniques used were observation, interviews and documentation which were then analyzed and tested for the validity of the data. The results of this research show that: (1) Archives planning in improving the quality of services at the Batu City Education Office consists of processes, namely determining targets, identifying archives, collecting archive data, determining archives, preparing archive processing guidelines, and preparing archive retention schedules. (2) The implementation of archives in improving the quality of services at the Batu City Education Service is carried out in several processes, namely managing letters, filing archives, implementing archive services, maintaining archives, and depreciating archives. (3) Then, the results of the archival evaluation in improving the quality of services at the Batu City Education Office are carrying out direct evaluations by directing and supervising the process of archival activities, providing direct input, holding training related to the use of digital applications, meeting infrastructure, and conducting related surveys with the service process.